Parameter Learning in General Equilibrium: The Asset Pricing Implications - Collin-Dufresne, Pierre; Johannes, Michael; Lochstoer, Lars A. (American Economic Review, 2016)
Parameter learning strongly amplifies the impact of macroeconomic shocks on marginal utility when the representative agent has a preference for early resolution of uncertainty. This occurs as rational belief updating generates subjective long-run consumption risks. We consider general equilibrium models with unknown parameters governing either long-run economic growth, rare events, or model selection. Overall, parameter learning generates long-lasting, quantitatively significant additional macroeconomic risks that help explain standard asset pricing puzzles. (JEL C52, D83, E13, E32, G12)